Anterior interosseous nerve palsy as a result of prolonged shoulder immobilisation. Issue 5 (14th May 2019) - Murphy, Evelyn Patricia; Fenelon, Christopher; Alexander, Michael; Quinlan, John
Abstract : This is a rare case of an anterior interosseous nerve (AIN) palsy in a patient as a result of a prolonged period of shoulder immobilisation. The patient had an open reduction internal fixation of a midshaft clavicle fracture. They subsequently underwent removal of metal due to symptomatic prominence of the metal work. The patient was in a shoulder immobiliser for a period of 5 months in total. They developed progressive AIN palsy as a result of a positional compression due to prolonged wearing of a shoulder immobiliser. This resolved with conservative management and careful observation.